Learning to Program: Going Pair-Shaped - Teague, Donna; Roe, Paul (Innovations in teaching and learning in information and computer sciences, 2007)
Students continue to struggle with learning to program. Not only has there been a significant drop in the number of students enrolling in IT courses, but the attrition rate for these courses continues to be significant. Introductory programming subjects in IT courses seem to be a stumbling block for many students. How do we best engage students in the learning of a programming language? How can our current teaching and learning methods be improved to provide a better experience for them? Issues that have a detrimental effect on students' learning outcomes include more than simply the cognitive. Although programming really is complex and difficult to learn, there are also cultural and social influences on students presenting to introductory computer science courses. This paper highlights the advantages of intensive collaboration between students by exploiting the students' own ability and desire to interact with their peers. Peer interaction can lead to very strong learning experiences. This paper reflects on the current approaches to teaching programming by the Queensland University of Technology (QUT), Australia, with a short summary of the current focus of QUT's first programming subject and the methods used to teach it. An overview is then given of the web-based Environment for Learning to Program (ELP) which provides scaffolding for students while learning to program. The authors propose the introduction of tools to present a collaborative environment for students to actively engage in the course material through interaction with each other.